Analysis of Shunted Screen Gravel Pack Process and Calculation of Friction in Deepwater Horizontal Wells. (12th December 2021) - Xu, Fei; Zhou, Shengtian; Zhang, Chong; Yu, Yi; Dong, Zhao
Abstract : Shunted screen gravel packing is a kind of technology which is difficult to complete gravel packing with the conventional method in low fracture pressure formation and long wellbore length condition. According to the characteristics of LS 17-2 deepwater gas field, the shunted screen packing tool was designed and the gravel packing process and packing mechanism were analyzed. The variation law of the flow friction, flow rate distribution in multichannel, and other parameters of the shunted screen gravel packing were analyzed and calculated. The friction calculation model of different stages of gravel packing was established. A gravel packing simulation software was developed to simulate the friction in different stages of shunted screen gravel packing. The parameters such as sand-dune ratio, pumping sand amount, packing length, and packing time in the process of packing were also calculated. In deepwater horizontal well gravel packing, the results show that the friction ratio of the string is the largest in the stage of injection and α -wave packing. While the friction increases rapidly in the stage of β -wave packing because the carrier fluid needs to flow through the long and narrow washpipe/screen annulus. Particularly when the β -wave packing is near the beginning of the open hole, the packing pressure reaches the maximum. The calculated results are in good agreement with the measured results of the downhole pressure gauge. The model and software can provide technical support for the prediction and optimization of gravel packing parameters in the future.